Stand composition and structure of Rubroshorea curtisii in a lowland Dipterocarp remnant forest of Bukit Tiban, Riau Islands, Indonesia - ARIDA SUSILOWATI; HENTI HENDALASTUTI RACHMAT; NELLY ANNA; DENI ELFIATI; FIFI GUS DWIYANTI; KOICHI KAMIYA; FAUZAN ALAWI; KESUMA WIJAYA; IDA MALLIA GINTING (Society for Indonesian Biodiversity, 2025)
Abstract. Susilowati A, Rachmat HH, Anna N, Elfiati D, Dwiyanti FG, Kamiya K, Alawi F, Wijaya K, Ginting IM. 2025. Stand composition and structure of Rubroshorea curtisii in a lowland Dipterocarp remnant forest of Bukit Tiban, Riau Islands, Indonesia. Biodiversitas 26: 4793-4804. Rubroshorea curtisii is an ecologically and commercially valuable Dipterocarpaceae species native to the Malay Peninsula, Peninsular Thailand, and northern Borneo, but in Indonesia its distribution is restricted to the Riau Islands. Habitat disturbances in this area directly threaten the species’ persistence. This study assessed the stand composition, structure, and floristic diversity of R. curtisii in Bukit Tiban Protected Forest, Batam Island, Riau Islands. Vegetation data were collected from 25 nested plots (20×20 m for trees, 10×10 m for poles, 5×5 m for saplings, and 2×2 m for seedlings) along five transects purposefully located in areas where R. curtisii occurs. All individuals were identified and measured to calculate relative density, frequency, basal area, and Importance Value Index (IVI), along with Shannon–Wiener diversity (H?), evenness (E), and species richness (R). A total of 44 species from 13 families were recorded, including seven Dipterocarpaceae species. Rubroshorea curtisii dominated all strata with the highest IVI values in seedlings (21.38%), poles (30.83%), and trees (34.00%), indicating its keystone ecological role. The stand exhibited an inverted J-shaped diameter distribution, characterized by a predominance of small-diameter trees (10-19.9 cm) and a scarcity of large individuals, reflecting regeneration imbalance. Diversity was highest in tree strata (H? = 3.10) and lowest in saplings (H? = 1.70), while evenness remained high (E = 0.91-0.97). Tree strata showed the highest richness (R = 7.05), whereas saplings had the lowest (R = 1.25). Despite ongoing regeneration, reduced mature individuals and disrupted recruitment suggest vulnerability to fragmentation, logging, and limited reproductive events. Conservation priorities should include protection of mature trees, enrichment planting, canopy restoration, and long-term monitoring of reproductive ecology. Integrating community participation and habitat rehabilitation is essential to ensure sustainable management of R. curtisii and the ecological resilience of remnant dipterocarp forests in the Riau Islands.